POLITICAL CONCEPTUAL METAPHORS IN POLITICAL DISCOURSES: A COGNITIVE SEMANTIC STUDY - Trisnendri Syahrizal (Eltin Journal : Journal of English Language Teaching in Indonesia, 2016)
This research is entitled Political Conceptual Metaphor in Political Discourses: A CognitiveSemantics Study. The study investigates the type of conceptual metaphor found in the politicaldiscourses. The discourses used as the data are taken from TIME Online Magazine duringFebruary 2015. Moreover, this study also tries to find out the conceptualizations of politics. Thisresearch analyzes the input of political domain and the input of other domains. This research also investigates the source and the target domain of structural metaphor of politics. In this study the researcher adapts several theories related to conceptual metaphor from Lakoff and Johnson, andEvans and Green. Moreover, this research also the theory from Fauconnier The result shows thatorientational metaphor is more common than ontological metaphor in the political discoursesunder the issue of 2016 general election. From 105 metaphorical statements, the researcher found42 orientational metaphors and 63 ontological metaphors. It shows that in the politicaldiscourses, politics commonly being projected as some concrete substances. Keyword: political conceptual methaphor, political discourse, cognitive semantics